Design and Development of a Web-Based Application for Managing Incoming and Outgoing Letters Using Agile Methodology - Masyhuri, Alif Syahda Adji; Rahmat, Basuki; Sari, Anggraini Puspita (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The management of incoming and outgoing correspondence in government institutions such as the Palesanggar Village Office is still carried out manually, leading to various problems such as delayed recording, difficulty in retrieving archived letters, and potential data loss. This study aims to develop a web-based Incoming and Outgoing Mail Information System to improve administrative efficiency and facilitate the archiving and reporting processes. Data were collected through direct observation, interviews with village officials, and literature review. The system development method used in this research is the Agile model, which consists of requirement analysis, system design, implementation, and testing phases. The result of this study is a web-based information system capable of recording, storing, and displaying data on incoming and outgoing letters in a structured manner and accessible to village staff. System testing shows that the application functions properly and is well received by users. The conclusion of this research is that the developed information system successfully addresses the issues of manual mail management and provides convenience and speed in archiving letter data at the Palesanggar Village Office.